Structural peculiarities of Pd-Cu-Ni-P and Pt-Cu-Ni-P metallic glasses as a reason for their significantly different room-temperature plasticity. (1st July 2023) - Louzguine-Luzgin, D.V.; Zanaeva, E.N.; Pratama, F.R.; Wada, T.; Ito, S.
Abstract: Structural features of the Pd42.5 Cu30 Ni7.5 P20 and Pt42.5 Cu27 Ni9.5 P21 metallic glasses are studied in the present work by high-resolution transmission electron microscopy. The results indicate that Pd42.5 Cu30 Ni7.5 P20 is a true bulk glass-former containing no crystalline particles/nuclei, while Pt42.5 Cu27 Ni9.5 P21 is a crystal growth-controlled type bulk glass-former which contains nanoparticles of about 1 nm size with a different chemical composition. These structural differences are manifested in room-temperature mechanical properties. Thermodynamic calculations are also used to support the observed features. Graphical abstract: Image, graphical abstract